Imperialisme Budaya Jepang Melalui Film Animasi Battle of Surabaya [Japanese Cultural Imperialism through Battle of Surabaya Movie Animation] - Pierre Mauritz Sundah (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2022)
Mass media as one of the means to develop culture has the function of cultural transmission, not only in the form of arts and symbols but also in the form of procedures, modes, lifestyles, and norms. Nowadays, movie animations out there mostly coming from the United States and Japan. In 2015, there is a local Indonesian movie animation that achieved national and international awards called the Battle of Surabaya. This movie animation tells the story of the Surabaya people independency movement on November 10th 1945. This research wants to describe how the form of cultural imperialism shown in local movie animation. The paradigm used in this research is the critical paradigm and a qualitative descriptive research. Data collection technique used are the in-depth interview, observation, and secondary-sources literature study technique. The informant for this research consists of a movie director, two audiences, and an academician who follows the development of movie animation in Indonesia. The results of this research shows that there are Japanese cultural hegemony shown in the Battle of Surabaya movie animation. Aside from using the anime style, Japanese cultural elements like foods, ethics, mores, and habits used to describe the daily life of Indonesian. This thing happens because Indonesian have been dominated by Japanese popular culture for a long time, especially anime.Bahasa Indonesia Abstract: Media massa sebagai salah satu sarana yang berfungsi untuk pengembangan kebudayaan, tidak hanya budaya dalam bentuk seni dan simbol tetapi juga budaya seperti tata cara, mode, gaya hidup dan norma-norma sehingga media memiliki fungsi cultural transmission. Saat ini, film animasi yang beredar di masyarakat lebih banyak merupakan film animasi luar terutama dari Amerika Serikat dan Jepang. Pada tahun 2015, terdapat film animasi lokal yang berhasil memperoleh penghargaan secara nasional dan internasional. Film animasi Battle of Surabaya menceritakan bagaimana perjuangan rakyat Surabaya 10 November 1945. Penelitian ini hendak menggambarkan bagaimana bentuk imperialisme budaya terlihat dalam film animasi lokal. Paradigma dalam penelitian adalah kritis dan merupakan penelitian kualitatif deskriptif. Teknik pengumpulan data yang digunakan adalah melalui in-depth interview, observasi dan studi literatur untuk sumber-sumber sekunder. Informan penelitian terdiri dari sutradara, dua orang penonton dan seorang akademisi yang mengikuti perkembangan film animasi di Indonesia. Hasil penelitian menunjukkan adanya hegemoni budaya Jepang terlihat dalam film animasi Battle of Surabaya. Selain menggunakan gaya anime, unsur budaya Jepang seperti makanan Jepang, etika, adat istiadat maupun kebiasaan dalam masyarakat Jepang digunakan dalam menggambarkan kehidupan sehari-hari masyarakat Indonesia. Hal tersebut terjadi karena masyarakat Indonesia telah lama didominasi oleh budaya populer Jepang terutama anime.